Estudo sobre desruptores endócrinos em sistemas aquáticos: detecção e perspectivas de tratamento das águas do Rio Aporé-MS/GO, utilizando-se adsorventes sólidos - Garcia, Edemir Feliciano [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Endocrine disrupters chemical (EDC), such as pesticides, represent an emerging class of contaminants in aquatic systems that can compromise the life of aquatic biota and human. Although some studies are being developed to quantify and verify the toxicity of EDC in the environment, there is almost no literature records related to the conduct studies and availability of these substances in surface waters. The aim of this study was to verity the presence of herbicide 2,4-D (diclorfenoxacetic acid), Atrazine and Linuron and insecticide Methyl Paration in Aporé River to propose perspectives of treatment in these waters by using low cost adsorbents. This river is located at the Brazilian savanna region, river that is located between Mato Grosso do Sul state and Goias state and receives a great amount of agricultural production waste. After collecting an amount of water at strategic points, has been done an extraction by the technical of Solid Phase Extraction, in cartridges of silica C-18, the detection in Gas Chromatography, attached with a detector Mass Spectrometry. The materials tested for the removal of pesticides, targeted in this study, were obtained from the: i) organically modified clays with surfactant N-dodecyl-2-pyrrolidone (Mo-DDP); ii) PET- Polyethylene terephthalate bottle after use (PET); III) biomass of J. curcas L. (TPMAN); iv) rice husk ash (RHA); v) silica gel organically modified with 2-Amino-1,3,4-thiadiazole (SGT) and vi) activated carbon from coconut shell (AC). Studies of detection and quantification of pesticides on the Aporé River‘s water demonstrate the presence of pesticides Malathion and Dibutyl phthalate(DBP), which are considered EDC by Brazilian, American and European government agencies. The adsorbents used had positive parameters to use for removal of these molecules, both in batch studies when fixed bed. The adsorption parameters tested showed that 60 to 120 min. ...

Desruptoress endócrinos (D.E), como por exemplo, os pesticidas, representam uma classe emergente de contaminantes em sistemas aquáticos, que pode comprometer a vida da biota aquática e de seres humanos. Embora alguns estudos estejam sendo desenvolvidos no sentido de quantificação e verificação da toxicidade dos D.E presentes no ambiente, praticamente não há na literatura registros de estudos associados ao comportamento e disponibilidade destas substâncias em águas superficiais. Este trabalho buscou determinar a presença dos herbicidas 2,4-D(ácido 2,4-diclorofenoxiacético), Atrazina e Linuron e do inseticida Paration Metil, considerados D.E pela literatura internacional, nas águas do Rio Aporé e propor perspectivas de tratamento de águas de sistemas hídricos por meio de adsorventes sólidos de baixo custo. Este rio está localizado no cerrado brasileiro, o qual é marco divisor do Estado de Mato Grosso do Sul com o Estado de Goiás e recebe grande carga de resíduos de produção agrícola. Após a coleta de amostras de água em pontos estratégicos, foi feita extração pela técnica de Extração em Fase Sólida, em cartuchos de sílica C-18 e a detecção em Cromatografia Gasosa acoplada com detector de Espectrometria de Massas. Os materiais testados para a remoção dos pesticidas alvo deste trabalho foram obtidos a partir de: i) argila organicamente modificada com o surfactante N-dodecil-2-pirrolidona (Mo-DDP); ii) garrafas de PET pós uso (PET); III) biomassa de pinhão manso - J. curcas L. (TPMAN); iv) cinzas de casca de arroz (CCA); v) sílica gel organicamente modificada com 2-Amino-1,3,4- thiadiazol (SGT) e vi) carvão ativado a partir de casca de coco (CA). Os estudos de detecção e quantificação dos pesticidas nas águas do Rio Aporé demonstraram a presença dos pesticidas Malation e Dibutilftalato, os quais são considerados D.E por órgãos governamentais brasileiro, ...
Keywords: Desreguladores endócrinos; Adsorção; Poluição; Pesticidas - Aspectos ambientais; Endocrine disrupting chemicals